Mutational analysis of the Hsp70 substrate‐binding domain: Correlating molecular‐level changes with in vivo function. Issue 6 (4th January 2021) - Xu, Linan; Zhang, Hong; Cuskelly, Daragh D.; Doyle, Sean; Perrett, Sarah; Jones, Gary W.
Abstract: Hsp70 is an evolutionarily conserved chaperone involved in maintaining protein homeostasis during normal growth and upon exposure to stresses. Mutations in the β6/β7 region of the substrate‐binding domain (SBD) disrupt the SBD hydrophobic core resulting in impairment of the heat‐shock response and prion propagation in yeast. To elucidate the mechanisms behind Hsp70 loss of function due to disruption of the SBD, we undertook targeted mutational analysis of key residues in the β6/β7 region. We demonstrate the critical functional role of the F475 residue across yeast cytosolic Hsp70‐Ssa family. We identify the size of the hydrophobic side chain at 475 as the key factor in maintaining SBD stability and functionality. The introduction of amino acid variants to either residue 475, or close neighbor 483, caused instability and cleavage of the Hsp70 SBD and subsequent degradation. Interestingly, we found that Hsp70‐Ssa cleavage may occur through a vacuolar carboxypeptidase (Pep4)‐dependent mechanism rather than proteasomal. Mutations at 475 and 483 result in compromised ATPase function, which reduces protein re‐folding activity and contributes to depletion of cytosolic Hsp70 in vivo. The combination of reduced functionality and stability of Hsp70‐Ssa results in yeast cells that are compromised in their stress response and cannot propagate the [ PSI + ] prion. Abstract : Hsp70 is a highly conserved molecular chaperone that allows cells to respond and survive following exposure to stress. Using Saccharomyces cerevisiae as a model system, we have identified key amino acid residues in the substrate‐binding domain of the protein that modulate Hsp70 function and how molecular level changes in protein structure translate through to phenotypic change in the stress response and prion propagation.